2020
DOI: 10.1186/s13040-020-00224-9
|View full text |Cite
|
Sign up to set email alerts
|

Network pharmacology reveals the multiple mechanisms of Xiaochaihu decoction in the treatment of non-alcoholic fatty liver disease

Abstract: Background: Non-alcoholic fatty liver (NAFLD) is a chronic disease worldwide, which poses a huge threat to human health. Xiaochaihu decoction is a well-known traditional Chinese medicine prescription. It has been proven effective in treating NAFLD but its mechanism is still unclear. Objective: Multiple mechanisms of Xiaochaihu decoction are explored by identifying and connecting potential targets and active ingredients in the treatment of NAFLD. Methods: Active ingredients and related targets of seven herbs we… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 41 publications
0
19
0
Order By: Relevance
“…The major indicators of DAI, the colon length, and the ratio of colon length/body weight have shown that DSS exposure can induce classic symptoms of colitis ( Ma et al, 2018 ; Zhao et al, 2019 ; Dong et al, 2020 ; Zhao et al, 2020 ). Over the years, components from Chinese medicinal plants L. hypoglauca and S. baicalensis were widely used for inflammatory diseases, including upper respiratory tract infection, acute and chronic tonsillitis, acute and chronic pharyngitis, and burn infection ( Marafini et al, 2019 ; Hu et al, 2020 ). In the present study, the colitis mouse model was established by drinking 3% DSS water for 7 days.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The major indicators of DAI, the colon length, and the ratio of colon length/body weight have shown that DSS exposure can induce classic symptoms of colitis ( Ma et al, 2018 ; Zhao et al, 2019 ; Dong et al, 2020 ; Zhao et al, 2020 ). Over the years, components from Chinese medicinal plants L. hypoglauca and S. baicalensis were widely used for inflammatory diseases, including upper respiratory tract infection, acute and chronic tonsillitis, acute and chronic pharyngitis, and burn infection ( Marafini et al, 2019 ; Hu et al, 2020 ). In the present study, the colitis mouse model was established by drinking 3% DSS water for 7 days.…”
Section: Discussionmentioning
confidence: 99%
“…Traditional Chinese medicine, extracted from medicinal plants, including Lonicera hypoglauca and Scutellaria baicalensis , showed anti-inflammatory and antioxidative functions ( Hu et al, 2020 ). Studies have shown that medicinal plants may contribute to inflammatory alleviation through inhibiting oxidative stress and regulating the gut barrier and gut microbiota ( Almousa et al, 2018 ; Bai et al, 2019 ; Xiao et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Traditional Chinese medicine (TCM) has unique therapeutic advantages in the treatment of a variety of complex diseases and major diseases, such as cholestasis, nonalcoholic fatty liver disease, liver fibrosis, and ischaemic stroke ( Jiang et al, 2020a ; Hu et al, 2020 ). The genus Tripterygium contains only 3 species, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Lingguizhugan could also mitigate NAFLD by suppressing the expression of INSIG1 and LPIN1 genes, indicating decreased oxidative stress, cholesterol biosynthesis, and triglyceride accumulation in the liver [ 82 ]. Among various decoctions, the Xiaochaihu, a combination of seven TCMs, is reported to regulate immunity metabolism and oxidative stress [ 83 ]. Further, the modified Xiaochaihu decoction could ameliorate age-associated NAFLD by downregulating mRNA/protein levels of core targets in lipid metabolism and inflammation-related pathways such as fatty acid synthase, acetyl-CoA carboxylase, IL-6, and nuclear factor- β [ 84 ].…”
Section: Treatment Strategies For Concomitant Liver Disease and Diabetesmentioning
confidence: 99%